Penerapan Cawisan sebagai Metode Dakwah dalam Memperkaya Wawasan Keislaman Remaja Masjid Sultan Mahmud Badaruddin Jayo Wikramo Palembang - Muhammad Akbar Al'anmi; Nurseri Hasnah Nasution; Anang Walian (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This research is entitled "The Application of Cawisan as a Da'wah Method in Enriching the Islamic Insight of Youth at Sultan Mahmud Badaruddin Jayo Wikramo Mosque, Palembang." The background of this research is the low religious understanding of youth who tend to be textual and have not been able to connect Islamic teachings with the reality of life. The research method used is descriptive qualitative, Data collection techniques in this study are observation, interviews, and documentation. The research consists of two types of sources, namely primary data and secondary data, using data analysis by means of data reduction, data presentation and drawing conclusions. Sultan Mahmud Badaruddin Jayo Wikramo Mosque has a local tradition called Cawisan, namely the oral da'wah method through lectures, discussions, and questions and answers that have long been developed in South Sumatra. This tradition is implemented in the development of the Palembang Grand Mosque Youth Association (IRMA) called fiqh studies and Dhuha Lectures to enrich adolescents' Islamic insights. This study aims to describe the implementation of the Cawisan method, its supporting and inhibiting factors, and adolescent responses to its implementation. Theoretically, this study uses Yusuf Al-Qardhawi's Dakwah Bil Lisan theory, which includes four forms of delivery: Bayan Syafahi, Bayan Tashrihi, Bayan Mujadalah, and Bayan I'lami, all of which are evident in the implementation of Cawisan. This study also refers to David Ausubel's Cognitive Theory, especially Meaningful Learning, which emphasizes the importance of linking new material to adolescents' cognitive structures through advance organizers and progressive differentiation. The results show that the Cawisan method is well implemented and structured, with direct interaction that makes the material easy to understand and apply. Supporting factors include adolescent enthusiasm, support from mosque administrators, and a religious environment. The obstacles are time constraints and inconsistent attendance. The response from teenagers was very positive because Cawisan was considered communicative and effective in increasing Islamic insight, faith, worship, and Islamic brotherhood.